Fungicidal control of the most common onion mycoses during the growing season - O. Borzykh; V. Sergienko; M. Dzham; O. Shyta; S. Mykhaylenko (Карантин і захист рослин)
Goal. To investigate the effectiveness of fungicidal control of the most common onion diseases during the growing season.